Morality as the Foundation of Legal Formation in Indonesia from the Perspective of Modern Legal Philosophy - Putra, Gilang; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
This study examines the relationship between public morality and the law-making process in Indonesia, focusing on the extent to which moral values are reflected in contemporary legislative practices. Theoretically, an ideal legal system should embody moral principles and prioritize justice and the public good. However, political realities often influence the legislative process, resulting in regulations that do not fully represent societal interests. Several laws enacted in the past two decades—such as the revision of the Anti-Corruption Law (UU KPK), the Mineral and Coal Law (UU Minerba), and the Omnibus Law on Job Creation (UU Cipta Kerja)—illustrate the dominance of political interests and the limited involvement of the public. The findings indicate that legislative practices frequently deviate from the principles of good regulatory formation as mandated by Law No. 12 of 2011 and its amendments, particularly concerning transparency, clarity of purpose, and public participation. Consequently, public trust in the House of Representatives remains low, as reflected in the 2025 survey by Indikator Politik Indonesia. This study underscores the importance of oversight mechanisms such as judicial review and highlights the need for more substantive public participation to ensure that legislation aligns with moral values and promotes social justice.